Uso de m. oleífera en pollos y su efecto en los parámetros productivos y económicos - Gonzalez Eras, Gloria Estefania (Machala : Universidad Técnica de Machala, 2022)
This research was carried out at the Santa Inés farm (Faculty of Agricultural Sciences, Universidad Técnica de Machala), El Oro Province, Ecuador. The main objective was to evaluate the effect of Moringa oleifera leaf meal on the productive and economic parameters of Cobb 500 chickens. For the biosecurity and well-being of the birds, a pre-established managemet for open-shed systems in the area was used, applying a basic vaccination schedule to the chickens. For the experiment, a Completely Random Design (CRD) was applied, using 200 Cobb 500, newborn mixed chickens (male and female), distributed in 5 treatments and evaluated for 35 days, each treatment had 4 experimental units of 10 chickens. The disposition of the groups was as follows: control (T1) to which only the basal diet; T2, T3, T4 and T5 in which 1, 2, 3, 4% of M. oleifera leaf meal was administered in the feed, respectively. The variables evaluated were: live body weight, feed consumption and accumulated water, feed conversion ratio, mortality, productive efficiency factor, kilograms of meat per square meters (m²) and economic expenses. To determine the possible differences, the statistical software Statgraphics Centurion XV.I. ®, was used. A parametric analysis of one factor (ANOVA), prior to the assumptions of normality and homogeneity was used. In order to discriminate among the means, the Bonferroni multiple comparison procedure was applied with a confidence level of 95%. The results showed that there is an effect on live weight and feed intake, because diets with an inclusion greater than 3% were negatively influenced in the first 3 weeks of life of the animal, while the rest of the variables were not affected.
Esta investigación se realizó en la granja Santa Inés (Facultad de Ciencias Agropecuarias, Universidad Técnica de Machala), provincia de El Oro, Ecuador. El objetivo principal fue evaluar el efecto de la harina de hojas de Moringa oleifera sobre los parámetros productivos y económicos de pollos Cobb 500. Para la bioseguridad y bienestar de las aves se utilizó un manejo preestablecido para los sistemas de galpones abiertos de la zona, aplicando un esquema básico de vacunación a los pollos. Para el experimento se aplicó un Diseño Completamente al Azar (DCA), utilizando 200 pollos mixtos (machos y hembras) recién nacidos Cobb 500, distribuidos en 5 tratamientos y evaluados durante 35 días, cada tratamiento contó con 4 unidades experimentales de 10 pollos. La disposición de los grupos fue la siguiente: control (T1) a los que se les administró únicamente la dieta basal; T2, T3, T4 y T5 a los que se les suministró 1; 2; 3; 4% de harina de hojas de M. oleifera en la alimentación, respectivamente. Las variables evaluadas fueron: peso vivo, consumo de alimento y agua acumulado, índice de conversión alimenticia, mortalidad, factor de eficiencia productiva, Kilogramos de carne por metros cuadrados y gastos económicos. Para determinar las posibles diferencias se utilizó el software estadístico Statgraphics Centurion XV.I. ®. Se empleó un análisis paramétrico de un factor (ANOVA), previo a los supuestos de normalidad y homogeneidad. Para discriminar entre las medias se aplicó el procedimiento de comparación múltiple de Bonferroni con un nivel de confianza del 95%. Los resultados mostraron que existe un efecto sobre el peso vivo y el consumo de alimento, debido a que las dietas con una inclusión mayor al 3% se vieron influenciadas negativamente en las primeras 3 semanas de vida del animal, mientras que el resto de las variables no se vieron afectadas.
Keywords: ÍNDICE DE CONVERSIÓN ALIMENTICIA; FACTOR DE EFICIENCIA PRODUCTIVO; PESO VIVO